Construction, validation and factor structure of greed questionnaire based on Islamic sources - Ahad Omidi; Mostafa Jahangiri (اخلاق وحیانی)
The aim of the current research was to construct, validate and determine the psychometric properties of the greed questionnaire based on Islamic sources from a psychological perspective. The research method was Siye and Shannon's qualitative content analysis of inductive type to analyze the data and survey method to make the questionnaire. The statistical population was students, 212 of whom were selected by stratified random sampling.   Content validity was obtained for the findings and the items created by humanities and psychology experts, each item with a minimum CVR of 0.99 and CVI index of 0.79 was selected. Construct validity was investigated by exploratory and confirmatory factor analysis using spss26 and Amos24 tools, and two factors of Mazmum and Mamdouh greed were discovered and confirmed with 16 items each. The reliability of the questionnaire was obtained with the correlation score of each item with Guttman's two-half method and the Spearman-Brown coefficient and Cronbach's alpha of Mazmum greed equal to (0.875) and Mamdouh greed equal to (0.864), which indicates a very good internal consistency. Greed questionnaire is based on Islamic sources. By confirming the validity and reliability of the greed questionnaire based on Islamic sources, researchers can use the greed questionnaire based on Islamic sources in research and psychological research to measure and quantify the trait of greed.